Webasto : co-creating innovation with lead users - Chesbrough, Henry William; Stern, Alexander (London : SAGE Publications Ltd, 2017)
In the book, Open Services Innovation, the concept of co-creation with ones customers is touted as a best practice for companies. This is also the prescription offered by the Lead User methodology built on the work of Eric von Hippel. There are a number of companies that have benefited from embracing the idea of co-creating with customers. And business school cases in general tend to discuss successful examples of various proffered concepts.This case is different. It is, in fact, a failure case, where a company faithfully followed a "best practice", and ended up with nothing to show for it. As such, it can be a powerful antidote to the usual success cases that comprise much of our syllabi.The Webasto case study provides students with an example of a company that focused on product innovation by incorporating a lead user method. Alexander Lang, director of marketing, created an elaborate open innovation process in order to help Webasto not only create innovative products, but also to differentiate itself as an innovative company. There are a number of interesting innovation, organizational, strategy, change management, and leadership issues this case brings up, all likely to generate a lively class discussion. As it happens, some of these issues prove fatal to the initiative.
Originally published in Chesbrough, H., & Stern, A. (2012). Webasto: Co-creating innovation with lead users. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Webasto (Firm); Technological innovations -- Case studies; Management -- Case studies